Golgi recruitment assay for visualizing small-molecule ligand–target engagement in cells. Issue 57 (15th June 2020) - Suzuki, Sachio; Ikuta, Masahiro; Yoshii, Tatsuyuki; Nakamura, Akinobu; Kuwata, Keiko; Tsukiji, Shinya
Abstract : A Golgi recruitment (G-REC) assay is developed as a new method for visualizing small-molecule ligand–target engagement in living cells. Abstract : The development of methods that allow detection of ligand–target engagement in cells is an important challenge in chemical biology and drug discovery. Here, we present a Golgi recruitment (G-REC) assay in which the ligand binding to the target protein can be visualized as Golgi-localized fluorescence signals. We show that the G-REC assay is applicable to the detection of various ligand–target interactions, ligand affinity comparison among distinct protein isoforms, and the monitoring of unmodified drug–target engagement in cells.